2015
DOI: 10.1097/spv.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Urinary Nerve Growth Factor Levels With Bladder Outlet Obstruction in Women

Abstract: Objectives Nerve growth factor (NGF) has been proposed as a urinary biomarker and previously shown to be elevated in male patients with bladder outlet obstruction (BOO) and other lower urinary tract symptoms. No published studies have examined NGF as a potential urinary biomarker in women with BOO. The aims of this prospective study were to evaluate NGF levels in urine from women with anatomic BOO resulting from pelvic organ prolapse (POP) and/or previous incontinence surgery and to measure the effect associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…In view of the fact that urinary biomarkers are increased in a wide spectrum of LUTS, the magnitude of variation of biomarkers' concentrations relative to a baseline or a cut-off value may be analyzed to provide insight about the underlying pathogenetic mechanisms of disease. As in the case of OAB, a similar degree of increase of NGF values was demonstrated in other pathologies such as BOO (3.71 fold increase relative to baseline values) 46 and urinary tract infections (UTI) (2.72 fold increase). 47 Interestingly, NGF saw significantly higher values in interstitial cystitis (IC) (34.5 fold increase).…”
Section: Urinary Biomarkerssupporting
confidence: 68%
“…In view of the fact that urinary biomarkers are increased in a wide spectrum of LUTS, the magnitude of variation of biomarkers' concentrations relative to a baseline or a cut-off value may be analyzed to provide insight about the underlying pathogenetic mechanisms of disease. As in the case of OAB, a similar degree of increase of NGF values was demonstrated in other pathologies such as BOO (3.71 fold increase relative to baseline values) 46 and urinary tract infections (UTI) (2.72 fold increase). 47 Interestingly, NGF saw significantly higher values in interstitial cystitis (IC) (34.5 fold increase).…”
Section: Urinary Biomarkerssupporting
confidence: 68%
“…They showed that these levels were significantly higher when compared with age-matched controls. After surgical correction, the urinary NGF/Cr levels significantly decreased 1 month after intervention 30 . In this study with a larger patient population, we observed that the urinary NGF increased at the 1- and 3-month postoperative follow-ups and decreased to a level similar to baseline at 6-month after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…At first glance PFR ≤7 mL/s would seem unlikely to be associated with high‐risk prostate cancer. However recent studies suggest an association between significantly greater increases in NGF and BOO or BOO and OAB compared with controls. These finding are especially important in the light of recent evidence linking nerve growth and NGF with prostate cancer in both mice and human studies .…”
Section: Discussionmentioning
confidence: 94%
“…The aim of the present study was primarily to evaluate whether there were significant improvements in PFR from baseline after RARP in men at risk of BOO, similar to those in men without BOO, and whether the improvements persist over long‐term follow up . Finally, because several reports have found an association between BOO and nerve growth factor (NGF), we explored whether this relationship resulted in a more aggressive prostate cancer.…”
Section: Introductionmentioning
confidence: 99%